Letter : Spain - Stolz, George
011-0082-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VI St/H Telegrams : inter fed-paris Telephone : invalides 45-88 AFFILIATED COUNTRIES : Argentine Austria Belgium Canada Czechoslovakia Dantzig Denmark Dutch East Indies Estonia Finland France Great Britain Greece Holland Hungary India Luxemburg Memel Territory Mexico Norway Palestine Poland Roumania South Africa South-West Africa Spain Sweden Switzerland Yugoslavia EXECUTIVE COMMITTEE : President : W. M Citrine, Great Britain Vice-Presidents : H. Jacobsen, Denmark ; L. Jouhaux, France : E. Kupers, Holland; Corn. M ertens, Belgium : R Tayerle, Czechoslovakia General Secretary : W Schevenels Letter sit. Espagne No. 238 10th June 1937. Mr. W. M. Citrine, LONDON. Dear Comrade Citrine, SPAIN With reference to your letter of the 7th June, I would inform you that, apart from the telegram of which we sent you a translation, no other communication has been received from Spain. As you will see from this week's "Bulletin", the Workers' Group also sent a telegram to the UGT and the Prime Minister of Spain, which I see from a letter received here yesterday have made a very good impression. Should a written communication be received, we will take the action you propose. Yours sincerely, G.Stolz, Assistant Secretary: 292/946/11/82